2012
DOI: 10.1109/tasl.2011.2162318
|View full text |Cite
|
Sign up to set email alerts
|

Speaker Diarization Error Analysis Using Oracle Components

Abstract: Abstract-In this paper we describe an analysis of our speaker diarization system based on a series of oracle experiments. In this analysis, each system component is substituted by an oracle component that uses the reference transcripts to perform flawlessly. By placing the original components back into the system one at a time, either in a top-down or bottom-up manner, the performance of each individual system component is measured. The analysis approach can be applied to any speaker diarization system that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In standard speaker diarization systems, which are based on iterative segmenting and clustering [23,12], each speaker is modeled by a GMM model and the segmentation is done using HMM-Viterbi decoding. More specifically, the system starts with K clusters 3 after front-end acoustic processing and removing non-speech segments.…”
Section: Resultsmentioning
confidence: 99%
“…In standard speaker diarization systems, which are based on iterative segmenting and clustering [23,12], each speaker is modeled by a GMM model and the segmentation is done using HMM-Viterbi decoding. More specifically, the system starts with K clusters 3 after front-end acoustic processing and removing non-speech segments.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the error rates of automatic speech processing systems increase when processing speech from multiple simultaneous speakers [8], [3]. Several diagnostical studies on speaker diarization systems have also shown that overlapping speech is one of the main sources of error in state of the art speaker diarization systems [9], [10], [11]. Several previous works have proposed methods to detect overlapping speech in meeting room conversations.…”
Section: Introductionmentioning
confidence: 99%
“…Several diagnostical studies were done to isolate the main sources of errors in speaker diarization systems [11,12,13]. These studies have shown that the significant sources of errors in a typical diarization system come from overlapping speech segments and errors in speech/non-speech detection.…”
Section: Introductionmentioning
confidence: 99%